Pullback Attractor for a Non-Autonomous Generalized Cahn-Hilliard Equation with Biological Applications - Duan, Ning (Mathematical Modelling and Analysis, 2016)
In this paper, we consider a non-autonomous generalized Cahn-Hilliard equation with biological applications. It is shown that a pullback attractor of the equation exists when the external force has exponential growth.